2002
DOI: 10.1124/jpet.301.3.1052
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ginsenoside Rg2 on Human Neuronal Nicotinic Acetylcholine Receptors

Abstract: Ginseng saponins, major active components of ginseng root used by folk medicine in the treatment of various diseases, produce multiple pharmacological responses having many effects on the central and peripheral nervous system. Specifically, ginsenoside Rg 2 has been shown to block the nicotinic acetylcholine receptors in bovine chromaffin cells. We have studied the effect of Rg 2 on different types of human neuronal nicotinic acetylcholine receptors (nAChRs), both homomeric and heteromeric, expressed in Xenopu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 30 publications
1
33
1
1
Order By: Relevance
“…Additionally, it has been shown that ginseng total saponins can modulate dopaminergic activity at both pre-synaptic and post-synaptic receptors (58); and they can block behavioral sensitization induced by psychostimulants such as morphine (59), cocaine (58), methamphetamines (60), and nicotine (61 -63). Furthermore, it was found that ginseng increased serotonin in the cortex (64), ginseng saponins raised the levels of biogenic amines in normal rat brain (65), ginsenoside Rg2 directly interacted with nicotinic receptor subtypes (66), and ginseng administration lead to regulation of GABAergic transmission in animals (67,68).…”
Section: Modulatory Effect Of Ginseng On Neurotransmissionmentioning
confidence: 99%
“…Additionally, it has been shown that ginseng total saponins can modulate dopaminergic activity at both pre-synaptic and post-synaptic receptors (58); and they can block behavioral sensitization induced by psychostimulants such as morphine (59), cocaine (58), methamphetamines (60), and nicotine (61 -63). Furthermore, it was found that ginseng increased serotonin in the cortex (64), ginseng saponins raised the levels of biogenic amines in normal rat brain (65), ginsenoside Rg2 directly interacted with nicotinic receptor subtypes (66), and ginseng administration lead to regulation of GABAergic transmission in animals (67,68).…”
Section: Modulatory Effect Of Ginseng On Neurotransmissionmentioning
confidence: 99%
“…23,24) However, ginsenosides Rg 3 had no effects on homomeric α7 nicotinic acetylcholine receptor. 21) Instead, Rg 3 inhibited mutant homomeric α7 nicotinic acetylcholine receptor, which was mutated at channel pore regions.…”
Section: Effect Of Rg 3 On I Ach In Oocytes Expressing α9α10 Nicotinimentioning
confidence: 99%
“…In previous studies, we have demonstrated that ginsenosides regulates subsets of nicotinic acetylcholine receptor channel activity such as α3β4 and other heteromeric nicotinic acetylcholine receptors. 23,24) Interestingly, Rg 3 had no effects on homomeric α7 nicotinic acetylcholine receptor. Although expression of the α9α10 nicotinic acetylcholine receptor is limited in several tissues, [9][10][11][12][13][14] little is known about the effects of Rg 3 on the α9α10 nicotinic acetylcholine receptor.…”
Section: Effect Of Rg 3 On I Ach In Oocytes Expressing α9α10 Nicotinimentioning
confidence: 99%
“…Additionally, it has been shown that ginseng total saponins modulates dopaminergic activity at both presynaptic and postsynaptic receptors 75) , and blocks behavioral sensitization induced by psychostimulants such as morphine 76) , cocaine 77) , methamphetamines 78) and nicotine 79) . Ginseng increased serotonin in the cortex 80) , ginseng saponins raised the levels of biogenic amines in normal rat brain 81) , ginsenoside Rg 2 directly interacted with nicotinic receptor subtypes 82) and ginseng administration led to regulation of GABAergic transmission in animals 83,84) .…”
Section: Effect On Neurotransmitter Changes By Ginsenosidesmentioning
confidence: 99%